The comparative study on acut renal toxicity of ionic and non-ionic contrast media in cell culture - Sibel Yavru; Nuri Yavru (Eurasian Journal of Veterinary Sciences)
In this study was carried out to show the damage of high osmolality ionic and low osmolality non-ionic contrast media in indirect radiography of kidneys, invitro. In this study MDBK was used as permanent cell culture. Omnipaque (lohexol) which is low osmolality non-ionic and Urografin 76 % (Diatrizoate) which is high osmolality ionic contrast media were used in different dilution con-cdntrations. As a result ionic contrast media even in low concentration produced CPE in kidney cell culture, but alternatively the same effect .was determined in non-ionic media after 24 hours without any dilution. CPE was not determined in cell cultures dilution of these media.